Study of Energy Performance in Malaysian Public Hospital using Power Query - Harun, Hasbullah (Information Management and Business Review, 2023)
In 2016, the Ministry of Health (MOH), Malaysia, initiated a sustainable program that includes activities for sustainable energy management at all 145 buildings under the MOH. The focus of the sustainable energy management program is to target these buildings to reduce their annual energy consumption by 10% by 2018. The target implementation of a sustainable energy management program includes achieving 3-star EMGS certification within 5 years. By December 2022, 135 have achieved two-star certification with the requirement to achieve at least 5% energy consumption savings. By 2019, the 118 buildings that embarked on EMGS certification had achieved 22.62% energy consumption savings. District and specialist hospitals achieved 23%–24% savings in 2019. The largest energy consumption in MOH buildings is for room cooling, which is contributed by air conditioning and mechanical ventilation (ACMV) equipment. The implementation of a sustainable energy management program has contributed to energy cost savings of RM21 million per year to MOH energy bills in 2019.